2020
DOI: 10.1177/0733464820940871
|View full text |Cite
|
Sign up to set email alerts
|

The CoreQ: Development and Testing of a Nursing Facility Resident Satisfaction Survey

Abstract: The development and testing of a nursing facility resident satisfaction survey (i.e., CoreQ) that could be used for public reporting purposes is presented here. This is important as very little satisfaction with care information is publicly available for nursing facility consumers. Validity testing is reported detailing the development of the CoreQ: Short Stay Discharge questionnaire and a measure that was calculated from the items in the questionnaire. This questionnaire resulted in four items whose combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…9,[17][18][19] The US Government Accountability Office recommended in 2016 that CMS evaluate the feasibility of adding consumer satisfaction survey results to the Five-Star system, 8 in line with studies that have found satisfaction surveys measure unique dimensions of nursing home quality. 20,21 Numerous surveys have been developed to measure nursing home satisfaction, though many are lengthy and/or not publicly available, 22 with the exception of some states' mandated surveys (eg, Minnesota, Ohio). [21][22][23] As another way to augment the star ratings, a consumer-based measure of quality has been studied, with evidence indicating consumers place value on several nontechnical dimensions (eg, attentiveness to residents, physical environment) not captured in the Five-Star system ratings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[17][18][19] The US Government Accountability Office recommended in 2016 that CMS evaluate the feasibility of adding consumer satisfaction survey results to the Five-Star system, 8 in line with studies that have found satisfaction surveys measure unique dimensions of nursing home quality. 20,21 Numerous surveys have been developed to measure nursing home satisfaction, though many are lengthy and/or not publicly available, 22 with the exception of some states' mandated surveys (eg, Minnesota, Ohio). [21][22][23] As another way to augment the star ratings, a consumer-based measure of quality has been studied, with evidence indicating consumers place value on several nontechnical dimensions (eg, attentiveness to residents, physical environment) not captured in the Five-Star system ratings.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 Numerous surveys have been developed to measure nursing home satisfaction, though many are lengthy and/or not publicly available, 22 with the exception of some states’ mandated surveys (eg, Minnesota, Ohio). 21 , 22 , 23 As another way to augment the star ratings, a consumer-based measure of quality has been studied, with evidence indicating consumers place value on several nontechnical dimensions (eg, attentiveness to residents, physical environment) not captured in the Five-Star system ratings. The researchers suggested adding such information to Care Compare, formerly Nursing Home Compare.…”
Section: Discussionmentioning
confidence: 99%
“…They developed a short, four-item survey measuring patient experience of care at skilled nursing facilities. The fourquestion survey produces valid and reliable data for distinguishing between facilities and is endorsed by the National Quality Forum (Castle et al, 2021).…”
Section: Reduce Questionnaire Lengthmentioning
confidence: 99%
“…The instruments cover almost all aspects of a resident`s experiences, such as room, staff, food, care services, activities, laundry, choice, nances, environment, engagement, administration overall rating, and so on. Across instruments, the number of factors or domains varied from as few as 4 [30], [33][34][35][36]. The median number of factors is six.…”
Section: Datementioning
confidence: 99%